(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1865)
This article describes the course of the embankment know as the ‘Devil’s Dyke’ that runs through Dumfries and Galloway. The author suggests that this dyke may have been used as a defensive feature intended to prevent the theft of livestock and argues that it was constructed around the year 1000 by the Anglo-Saxon people who lived in the East , to protect their livestock from the Celtic people who lived in the West .